Ganglion cell layer thinning in prodromal Alzheimer's disease defined by amyloid PET. Issue 1 (1st January 2019) - López‐de‐Eguileta, Alicia; Lage, Carmen; López‐García, Sara; Pozueta, Ana; García‐Martínez, María; Kazimierczak, Martha; Bravo, María; de Arcocha‐Torres, María; Banzo, Ignacio; Jimenez‐Bonilla, Julio; Cerveró, Andrea; Rodríguez‐Rodríguez, Eloy; et al.
Abstract: Introduction: The objective of this study was to investigate and compare optic nerve and retinal layers in eyes of patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) with paired control eyes using optical coherence tomography. Methods: Sixty‐three eyes of 34 subjects, 12 eyes with AD and 51 eyes with MCI, positive to 11 C‐labeled Pittsburgh Compound‐B with positron emission tomography ( 11 C‐PiB PET/CT), and the same number of sex‐ and age‐paired control eyes underwent optical coherence tomography scanning analyzing retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), Bruch's membrane opening–minimum rim width (BMO‐MRW), inner plexiform layer (IPL), outer nuclear layer, and lamina cribrosa (LC). Results: Compared with healthy controls, eyes of patients with positive 11 C‐PiB PET/CT showed a significant thinning of RNFL ( P  < .028) and GCL ( P  < .014). IPL and outer nuclear layer also showed significant thinning in two ( P  < .025) and one location ( P  < .010), respectively. No significant differences were found when optic nerve measurements BMO‐MRW and LC were compared ( P  > .131 and P  > .721, respectively). Temporal sector GCL, average RNFL, and temporal sector RNFL also exhibited significant thinning when MCI and control eyes were compared ( P  = .015, P  = .005 and P  = .050, respectively), and also the greatest area under the curve values (0.689, 0.647, and 0.659, respectively). GCL, IPL, and RNFL tend to be thinner in the AD group compared with healthy controls. Discussion: Our study suggests that RNFL and GCL are useful for potential screening in the early diagnosis of AD. LC and BMO‐MRW appear not to be affected by AD.